PENINGKATAN PARTISIPASI MASYARAKAT MELALUI PEMANFAATAN BSF DALAM PENGELOLAAN SAMPAH ORGANIK MENJADI PAKAN TERNAK DAN PUPUK ORGANIK - Elvania, Nindy Callista; Heri Mulyanti; Eka Luluk Fitriani; Reva Putri Sugianti (Universitas Kadiri, 2025)
The problem of household organic waste remains an environmental issue that requires effective management in various regions, including Jelu Village. This community service activity aims to increase active community participation in organic waste management through the use of Black Soldier Fly (BSF) larvae. BSF cultivation technology was chosen because it can quickly decompose organic waste and produce by-products in the form of animal feed and organic fertilizer. This program was implemented through an educational approach, technical training, and direct mentoring for residents from several neighborhood units (RT) in Jelu Village. The results of the activity showed an increase in community knowledge and skills in BSF cultivation, with maggot production reaching 2 kg in three weeks and daily organic waste management of around 4–5 kg. Furthermore, the community was also able to independently build cultivation cages. This activity has succeeded in raising ecological awareness while providing economic benefits, and is expected to become a model for sustainable organic waste management at the village level.